Analisis manfaat pengelolaan keuangan daerah bagi kesejahteraan masyarakat di Kabupaten Manggarai NTT - Maria Kurniawati Jani; Norman Duma Sitinjak; Risnaningsih Risnaningsih (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2021)
This study examines the role of financial management for the welfare of society. The research was conducted by means of Participatory Action Research in order to be more detailed, tangible in data collection and better understand the existing situation. The data source is secondary. The year of observation is 2014 to 2017. The results of the research are that better regional financial management will improve the welfare of the community. The research location is Manggarai Regency.